HUBUNGAN JAM KERJA DENGAN PENDAPATAN DRIVER GRAB - I Gede Wisnu Segara; Kadek Rai Suwena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
The purpose of this research was to determine the hours of work and income of GRAB drivers in the Singaraja City, Bali and the relationship between hours of work and the income of GRAB drivers in the Singaraja City, Bali. This type of research was quantitative research using a correlation research design. The population of this research were GRAB drivers in the Singaraja City as many as 1275 people. The sample of this study was determined using the Slovin formula obtained as many as 304 GRAB drivers in the Singaraja City. Data collection using questionnaires was analyzed using descriptive analysis and Pearson Product Moment correlation analysis assisted by SPSS 24.0 for Windows. The results showed that the hours of work of GRAB drivers in the Singaraja City, Bali in the high category were 26 people (8.55%), enough categories were 178 people (58.55%) and the low category were 100 people (32.89%), GRAB driver income in the Singaraja City, Bali in the very high category were 20 people (6.58%), high category were 26 people (8.55%), enough categories were 154 people (50.66%), low categories were 86 people (28.29%) and very low categories were 18 people (5.92%), and hours of work had a significant relationship to GRAB driver income in Singaraja City, Bali, as indicated by a correlation value of 0.787 with a significance value 0,000 smaller than α = 0.05.